The geysers of Yellowstone - Bryan, Scott (University Press of Colorado, 2008)
This revised popular field guide describes in detail each of the more than 500 geysers in Yellowstone National Park. With updated information and a new foreword by park archivist Lee Whittlesey, Geysers of Yellowstone is both a reference work and a fine introduction to the nature of geyser activity for the newcomer to geothermal phenomena. A glossary of key terms is provided, along with a comprehensive appendix that discusses other geyser areas of the world.